If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-2 + 4x) + -1(3 + -4x) + 5 = -1(-3 + 6x) + x + 1 (-2 * -1 + 4x * -1) + -1(3 + -4x) + 5 = -1(-3 + 6x) + x + 1 (2 + -4x) + -1(3 + -4x) + 5 = -1(-3 + 6x) + x + 1 2 + -4x + (3 * -1 + -4x * -1) + 5 = -1(-3 + 6x) + x + 1 2 + -4x + (-3 + 4x) + 5 = -1(-3 + 6x) + x + 1 Reorder the terms: 2 + -3 + 5 + -4x + 4x = -1(-3 + 6x) + x + 1 Combine like terms: 2 + -3 = -1 -1 + 5 + -4x + 4x = -1(-3 + 6x) + x + 1 Combine like terms: -1 + 5 = 4 4 + -4x + 4x = -1(-3 + 6x) + x + 1 Combine like terms: -4x + 4x = 0 4 + 0 = -1(-3 + 6x) + x + 1 4 = -1(-3 + 6x) + x + 1 4 = (-3 * -1 + 6x * -1) + x + 1 4 = (3 + -6x) + x + 1 Reorder the terms: 4 = 3 + 1 + -6x + x Combine like terms: 3 + 1 = 4 4 = 4 + -6x + x Combine like terms: -6x + x = -5x 4 = 4 + -5x Add '-4' to each side of the equation. 4 + -4 = 4 + -4 + -5x Combine like terms: 4 + -4 = 0 0 = 4 + -4 + -5x Combine like terms: 4 + -4 = 0 0 = 0 + -5x 0 = -5x Solving 0 = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 0 + 5x = -5x + 5x Remove the zero: 5x = -5x + 5x Combine like terms: -5x + 5x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| -29+56= | | -4x-1+5x=-13 | | j/20=3 | | 3(x+8)=3x+24 | | x/4+2=-2 | | 22=6+2x | | k+4/2=k+9/2 | | (5x+4)(x-1)=2 | | k+4/2=k+9/4 | | -7x+2+4x=2 | | 40=12x+4 | | 2x-x+3+3x=x+13 | | -7x+2+5x=2 | | 6x^2+5x=-1 | | (2x-5)/3=(2-5x)/7 | | 22+x=12 | | 4(2x-8)=1/7(49x+70) | | 37g^8-37h^8= | | 19+x=2 | | x+x+16+3x=211 | | x^3+4x^2=7x+28 | | 1+2x+2x=49 | | 733=P(1+0.01)3 | | A=P(1+r)N | | 1/3x-15=18 | | 22=6f-8 | | -6=-1 | | -30+7x=26+3x | | 1-x=2(0,5-0,5x) | | 7x+8+x=-24 | | x^8-3x^7=x^6-3x^5 | | (d-4/4)^2=16 |